Anak Berhadapan Hukum Ditinjau Dari Aspek Psikologi Hukum - Widya Romasindah Aidy (Jurnal Hukum Sasana, 2021)
Children as a mandate as well as the gift of God Almighty, we must always guard because in him the inherent dignity, dignity and rights as human beings must be upheld and basically, the occurrence of juvenile delinquency shows that there is an indiscipline of adolescents to the rules and norms that apply, both the family, school, community and self-norms as individuals, and the planting of these norms must certainly be given to adolescent individuals so that they have a good understanding of these norms. The purpose of this study is expected to be able to understand children who are dealing with the law in terms of legal psychology. The method used in this study is a normative juridical research method and analyzed data qualitatively by means of literature study, namely studying, understanding, identifying and recording literature, legislation and data relating to research problems so that it can be concluded that in dealing with children facing the law there is a need for a psychological approach in the law that refers to the application of specific legal psychology in the law in analyzing the causes of violations committed by children and the cause of lawbreakers who are still children or juvenile offenders.